Quem não senta pra aprender, não levanta para ensinar: uma aula com a Griot Marise de Santana - Santos, Vanessa (Quitéria) Caroline Silva (2019)
The following interview, carried out at ODEERE, brings reflections by Griot Marise de Santana regarding her struggles involving academic career, Afro-Brazilian religiosity and aspects of her ancestry strongly nuanced in her teaching, research and militant practice. We sought to make a presentation of his academic trajectory in a non-linear way, the spaces occupied by it, the repercussions of his research, as well as his theoretical connection with other and other Brazilian and Afro-Brazilian intellectuals. Finally, it points out the need for further studies in the field of Ethnic Relations and contemporaneity that have as their primary objective the colonization of knowledge and sciences. Keyword: Marise de Santana